Clinical Features of Human Parvovirus B19-Associated Encephalitis Identified in the Dakar Region, Senegal, and Viral Genome Characterization - Al Ousseynou Seye; Fatou Kiné Top; Maimouna Mbanne; Moussa Moise Diagne; Ousmane Faye; Amadou Alpha Sall; Ndongo Dia; Jean-Michel Heraud; Martin Faye (Viruses)
Neurological manifestations associated with human parvovirus B19 (B19V) infections are rare and varied. Acute encephalitis and encephalopathy are the most common, accounting for 38.8% of all neurological manifestations associated with human B19V. Herein, we report on the clinical features of 13 laboratory-confirmed human cases of B19V-associated encephalitis in Senegal in the framework of a hospital-based surveillance of acute viral encephalitis conducted from 2021 to 2023. Overall, B19V was detected from 13 cerebrospinal fluid samples using specific real time PCR. The mean age was 16.7 years among B19V-positive patients, with a higher prevalence in 0–5-year-old children and the sex ratio (male/female) was 2.25. The B19V-positive patients mainly exhibited hypoleukocytosis, normal glycorrhachia, and normal proteinorrachia in the cerebrospinal fluid. While the main neurological symptoms included meningeal and infectious syndromes. Furthermore, three complete B19V genome sequences were successfully characterized using next-generation sequencing. The newly characterized sequences belonged to the genotype 1a and represent, to date, the first complete B19V genome sequences from Senegal. These sequences could be useful not only in future phylodynamic studies of B19V but also in the development of prevention or treatment countermeasures. Our study is noteworthy for the identification of acute B19V-associated encephalitis in Senegal More investigations on the risk factors associated with B19V transmission in Africa are warranted.